Karakterisasi Muatan Nanopartikel Silika (SiO2) dengan Metode Elektroforesis - Santoso, Purwoko Haryadi; Kurniawan, Yohanes; Pamungkas, Havid Noor; Suparno, Suparno (Department of Physics, Sebelas Maret University, 2021)
Electrophoresis is one of the experimental methods employed in this study to characterize unique properties of charges of silica nanoparticles (SiO2) by observing their electrophoretic phenomena while they are situated in the electric field. This study is aimed to measure one of the SiO2 properties, namely the charge, using electrophoresis method through the variation of electric fields. The charge dependencies of SiO2 was probed towards five times variation of electric fields 1000, 1250, 1500, 1750, and 2000 V/m in 20 mL of aquades. The displacement of SiO2 could be observed through the light microscope with 160x magnification which the recorded observations then were analyzed by timeline-based software to measure the displacement time of particles during the observation. The results revealed that silica nanoparticles have the kind of positive charges in the colloidal solution. It is caused the magnitude of SiO2 charges is ranged constantly despite the variational effect of electric field in the environment. Light microscope has been optimized in this study to measure the velocity of SiO2 that tends to increase with respect to the magnifying electric fields given in the experiment.